THE RELIGIOUS MEANING OF ISLAMIC INSCRIPTION IN KOTA TINGGI CEMETERY, SIAK, RIAU PROVINCE - Burhanuddin, Dede (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2017)
This research discusses religious inscription found on the cemetery site in Kota Tinggi Siak Riau Province. The background of this research is based on the changes in the Malay tradition of Islam. Nuanced religious buildings (material culture) such as mosques, tombs and other buildings have undergone substantial changes, some even total changes, one of which is the replacement of Arabic calligraphy in the mosque or cemeteries with new ones. Whereas, before, it is the pride of the people about their Islamic tradition in the past. Many things become historical documents of development, social, cultural and community traditions in Siak. Inscriptions in the environment Kota Tinggi Cemetery contains data about the Kings, his royal family and the commanders of Siak Kingdom. This can help in discovering the history of the old Siak Kingdom, both from the genealogy of the Kings, the process of the establishment of the Siak Kingdom, its genealogy, development of the Islamic region and other sources. The inscriptions found in this area reveal the religious traditions of the Siak society at that time. Moreover, it can be used as evidence on the proximity between the Siak Kingdom and the teachings of Islam. Not all of the available contents of the inscriptions can be revealed in this research. This study uses archaeological research in the form of data collection, both literature data and field data obtained through the method of assessment, survey and related research, data processing techniques classification by type, material, location, dimensions and others. Interpretation or meaning of the data obtained through those stages are then incorporated with data obtained through the help of scientific historical analogies (historical), ethnographic, and experiment. However, given technical limitations, this study will only be analyzed through a historical approach.